New materials for sports equipment made of anisotropic fiber-reinforced plastics with stiffness related coupling effect - Kaufmann, J. (Procedia Engineering, 2015)
Fiber-reinforced plastics (FRP) are often used in sporting goods to increase their lightweight degree. Symmetric laminate are mostly used because of the complex deformation effects of asymmetric multi-layer Structures (MLS), which are also hard to handle in the complete production process. In the board sports industry almost all products are made out of symmetric biaxial or triaxial glass fiber fabrics to increase the stiffness and strength of the sandwich composites. Carbon fiber-reinforced plastics (CFRP) are used to reduce the high performance products` weight. FRP are also well suited to integrate additional functions. An uncommon way for such integration is the use of the material intrinsic anisotropic coupling effects of asymmetric MLS. Based on these deformation effects of FRP an all-new snowboard with the so-called anisotropic layer design technology (A.L.D.-tech) was developed at the Institute for Structure Lightweight, Technische Universität Chemnitz. In this product the anisotropic coupling effects are used for implementing a riding specific deformation of the snowboard to increase the customer value. At present, the spin-off silbaerg TM Snowboards uses three different levels of the A.L.D.-tech for the worldwide first serial products with such coupling effects; snowboards made of glass and carbon fiber reinforced sandwich structures. By varying the fabric material and the lay-up of the A.L.D.-tech MLS, different characteristics of the riding specific deformation are adjustable. For developing and computing this all-new type of board sport product the researchers used a numerical approach using a Finite Element Method (FEM) software solution provided by ANSYS. The model based on the Classical Laminate Theory (CLT) and focuses also the failure assessment by using Cuntze's failure criteria [1]. The ABD-Matrix of the CLT provides a good tool to visualize the different deformation effects of asymmetric MLS, which depends on the disc-plate problem. Due to this an A.L.D.-tech MLS with an unusual bending-curvature or bending-torsion coupling was developed, verified and launched into the market. This paper contains the description of different fabric material and lay-up combinations to adjust the grade of the anisotropic coupling of the snowboard as well as the integration of stitched sensors to measure the deformation while riding the snowboard. The comparison between numerical solution and experimental verification tests confirm the accuracy of the numerical model.